Association between socio-demographic characteristics and preventable lifestyle related risk factors of non-communicable diseases among adolescents: a school based study in Berhampur, Odisha - Karmee, Nivedita; Satapathy, Sushree Priyadarsini; Tripathy, Radha Madhab (International Journal Of Community Medicine And Public Health, 2017)
Background: Currently, the health scenario is riddled with the burden of non-communicable diseases. Life style related risk factors established during adolescents may extend into adulthood and may increase risk for non-communicable diseases. So this study was undertaken to ascertain the association of life style related risk factors for Non communicable diseases and socio demographic characteristics among adolescents. Methods: A cross-sectional study was conducted in Berhampur, Odisha. A total of 400 school children were included in the study. Data was collected by pre-tested, structured, close-ended, self-administered questionnaires. Data was entered and analysed using SPSS V.17.Descriptive statistics, chi square test and logistic regression analysis test were applied. Results: Out of 400 students included in the study, 69.5% were males. The mean age of the study subject was 15.77 with S.D 2.81. On multiple regression analysis, it was found that male respondents parents job had strong association with unhealthy dietary practices and educational status of respondents had strongest association with passive smoking and addictions habits. Conclusions: The present study showed a poor practice of healthy lifestyle with a high burden of lifestyle‑related risk factors of NCDs among students. Therefore, the schools should emphasize on including topics related to leading of a healthy life style in the curriculum. Frequent campaigns and educational seminars can be conducted for the adoption of healthy lifestyle.